On the substructure countability of graph neural networks - XIA, Wenwen (Institutional Knowledge at Singapore Management University, 2022)
With the empirical success of Graph Neural Networks (GNNs) on graph-related tasks, it is intriguing to investigate their theoretical power on these tasks. In this paper, we focus on GNNs' theoretical power on substructure counting, a fundamental yet challenging task in many applications. Previous works have proven that the 2-dimensional Weisfeiler-Leman algorithm (2-WL) equivalent GNNs can only count limited substructures. However, the substructure counting ability of theoretically more powerful and computationally tractable GNNs remains unclear. In this paper, we study conditions for substructures to be theoretically countable by k-WL equivalent GNNs, and then focus on 3-WL equivalent ones, which are currently the most theoretically powerful instances with practical computational cost. Further, we propose an algorithm to determine the countability of substructures for 3-WL equivalent GNNs. Our results reveal that 3-WL equivalent GNNs can count considerably more substructures than 2-WL equivalent ones. However, the proportion of countable patterns and prediction performance decrease as the pattern size increases. Therefore, we propose a Layer Permutation Pooling (LPP) model for better substructure counting performance. LPP first decomposes the data graph into subgraphs. Then we propose a layer permutation scheme to represent each decomposed subgraph as a set of matrices. Finally, LPP utilizes a neural network to conduct predictions on matrices. We compare LPP with several state-of-the-art GNNs on various datasets. Experimental results show that LPP outperforms baselines by 84% on average with the RMSE metric.